CHRONOTOPIA OF STORYTELLING IN UZBEK LITERATURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
One direction of last year's critical activity is the interpretation of creative research specific to the literary process. In this respect, the book by the teacher munakkid Umarali Normatov “the temperature question of the Creator " is characteristic. This collection consisting of four sections includes literary-critical articles, essays, memorabilia and literary conversations of written in the last three or four years. In addition to the achievements of the scientist in his observations on literary criticism, he also touched upon certain shortcomings. In particular, attention will be paid to the fact that today's criticism is to some extent lagging behind the literary process, the works created, first of all, the works capable of renewing artistic thinking – are not invented by literary criticism, the possibility of qualifying is limited and other aspects. Alternatively, the controversy last year in the journal